(untitled) (De Rebus Antiquis, 2020)
This paper is going to analyze a passage of the Praeceptum deliberativae materiae, a rhetorical text written by Emporius in V/VI century A.D., where Caesar is claimed to be Graecae exercitationis expers; such a so strange definition has its roots in the controversy of the populares against the Hellenization of the nobilitas: from a popularis perspective the real vir Romanus had to prefer the military skill to the rhetorical one, as C.Marius had done, and had to acquire his rhetorical skill in Latin, non in Greek, as the Rhetorica ad Herennium advised. Then being Graecae exercitationis expers was a quality requested to a leader of the populares, as Caesar wanted to be recognized, and we can retrace its origin in the literary propaganda of the Caesarian party, above all in Sallust’s Bellum Iugurthinum and in the Anticato of Caesar himself.